Concentrations of aripiprazole and dehydroaripiprazole in hair segments from deceased individuals with mental disorders. (December 2020) - Rygaard, Karen; Linnet, Kristian; Banner, Jytte; Johansen, Sys Stybe
Highlights: Segmental hair analysis of 18 deceased individuals with mental disorders. Concentrations of aripiprazole and dehydroaripiprazole in 6 × 1 cm hair segments. Stable aripiprazole concentrations in hair segments over a six month period. Positive correlations between concentrations in hair and postmortem blood. Abstract: Segmental hair analysis provides information regarding previous long-term drug exposure, which is useful in the evaluation of cause of death for individuals with mental disorders. The aim was to analyze postmortem concentrations of the antipsychotic drug aripiprazole and its active metabolite dehydroaripiprazole in hair segments from individuals with known aripiprazole intake. Hair samples were collected during autopsy. Each sample was segmented into one to six 1 cm segments, depending on the length of the hair shaft. Pulverized hair was extracted and analyzed using a previously published ultra-high-performance liquid chromatography–tandem mass spectrometric method. The 10th–90th percentile of aripiprazole concentrations in all hair segments (n = 78) from 17 individuals were 0.024 ng/mg–11 ng/mg with a median of 2.3 ng/mg, and the 10th–90th percentile concentrations of dehydroaripiprazole were 0.020 ng/mg–11 ng/mg, with a median of 2.6 ng/mg, in all hair segments (n = 71). The metabolite-to-parent drug ratios ranged from 0.21 to 1.5, with a median of 0.72. The administered doses were calculated for each individual based on aripiprazole prescription data and pharmacy pickups, giving dose estimates of 1 mg – 32 mg daily. A positive significant correlation was observed between concentrations in hair and blood, whereas no trends were observed between the concentrations in hair and the estimated doses. Besides aripiprazole, other antipsychotic drugs were found in several hair segments, indicating a high degree of polypharmacy among all subjects. The present study establishes concentrations of aripiprazole and dehydroaripiprazole in hair segments from 17 deceased individuals with long-term aripiprazole use. In addition, hair analysis demonstrates the possibility of evaluating polypharmacy.